Total Cost of Ownership (TCO) and Value Stream Mapping (VSM) Analysis for Cost Added Optimization in the Sunflower Supply Chain - Aldi Adi Pratama; Ario Usman Maulana (Countable (Contemporary Business and Sustainability Science), 2025)
PT XYZ faces a crucial problem in the inefficiency of its sunflower supply chain, particularly the lack of clarity regarding the structure of additional costs associated with activities. The high frequency of partial deliveries from farmers triggers an accumulation of storage and production costs, and a decline in seed quality due to repeated handling. On the other hand, insufficient coordination with seed suppliers causes harvest delays and additional storage costs, compounded by scarcity factors. This research uses a quantitative integration method of Total Cost of Ownership (TCO) and Value Stream Mapping (VSM). The TCO analysis results show the impact of raw material scarcity. Under normal conditions, the TCO per ton of oil reaches Rp 38.5 million. However, it surges by 65.4% to Rp 63.7 million per ton during scarcity. After optimization, this value was successfully reduced to Rp 52.4 million per ton. Meanwhile, VSM identified hidden time waste valued at Rp 117.3 million per month (8.3% of total costs), with procurement (48%) and receiving (31%) as the main contributors. Through Value Stream Costing (VSC)-based optimization, the potential savings could reach Rp 176.2 million per month (12.4% of total costs), sourced from lead time efficiency (Rp 37.6 million) and yield improvement (Rp 138.6 million).